PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD MUHAMMADIYAH 10 PALEMBANG - Kurnia Kurnia; Dian Nuzulia Armariena; Rury Rizhardi (Universitas Negeri Medan, 2022)
Abstract : The effect of the Numbered Head Together learning model on mathematics learning outcomes of Students in class III SD Muhammadiyah 10 Palembang. The purpose of this study was to determine whether there was an effect of the Numbered Head Together learning model on the mathematics learning outcomes of third grade students at SD Muhammadiyah 10 Palembang. This type of research is quantitative by using the type of research Quasi Experimental Design with the form of design used in this study is the Nonequivalent Control Group Design. The sampling technique used is the total sample technique. In the final analysis of the calculation using the paired sample t-test hypothesis test, the data obtained a significant value (2-tailed) 0.000 <0.05 and with a 95% confidence level this shows H0 is rejected and Ha is accepted the average value of learning outcomes before and after using Numbered Head Together increased from an average value of 46 to 77, which means that there is an influence of the Numbered Head Together learning model on the mathematics learning outcomes of third grade students of SD Muhammadiyah 10 Palembang.Keywords: Numbered Head Together, Learning Outcomes, MathematicsAbstrak : Pengaruh Model pembelajaran Numbered Head Together terhadap hasil belajar matematika siswa kelas III SD Muhammadiyah 10 Palembang. Tujuan penelitian ini adalah untuk mengetahui apakah model pembelajaran Numbered Head Together berpengaruh terhadap hasil belajar matematika kelas III SD Muhammadiyah 10 Palembang. Jenis penelitian ini ialah kuantitatif dengan mengunakan jenis penelitian Quasi Eksperimental Desaign dengan bentuk desain yang digunakan dalam penelitian ini adalah Nonequivalent Control Group Desaign. Teknik sampling yang digunakan yaitu teknik sample total. Pada analisis akhir perhitungan Dengan menggunakan uji hipotesis uji t sampel berpasangan diperoleh data nilai signifikan 0,000 < 0,05 dengan tingkat kepercayaan 95% hal ini menunjukan bahwa H0 ditolak dan Ha diterima sebagai rerata hasil belajar sebelum dan sesudah menggunakan Numbered Head Together meningkat yaitu dari nilai rata rata 46 menjadi 77 yang artinya terdapat pengaruh model pembelajaran Numbered Head Together terhadap hasil belajar matematika siswa kelas III SD Muhammadiyah 10 Palembang.Kata Kunci: Numbered Head Together, Hasil Belajar, Matematika